INNOVATIVE TECHNOLOGIES IN SOLVING PROBLEMS OF DESERTIFICATION AND DEGRADATION OF SOILS IN TURKMENISTAN - Гінкул, А. П.; Кривільова, С. П. (Municipal economy of cities. Series: «Economy science», 2018)
The article is devoted to solving one of the main environmental problems of the world-land degradation and desertification. The main types of desertification are listed. The main man-caused and anthropogenic causes of land degradation and desertification in the country have been determined to date. Traditional methods of combating degradation and desertification are considered, as well as innovative technologies in land reclamation and in the system of rational nature management in Turkmenistan for solving these problems. The problem of soil degradation and desertification is considered not only at the level of one country, but also at the global level. Also the main way to fight with this problem is to inform the public and provide qualified personnel. Keywords: soil degradation, desertification, land devastation, technogenic, anthropogenic, global, reclamation, salinization, ground water, struggle, innovative technologies of land reclamation.